English solo keyboard music of the middle and late baroque - Cooper, BAR (1974)
The music covered in this study contains much more variety, interest and artistic skill than one might be led to believe by most histories of music, even though certain standard forms prevail throughout the period. In the field of harpsichord music, the period coincides more or less exactly with the rise and fall of the suite, Almands, corants and sarabands started to be grouped into suites---very loosely at first---in about the 160s, and William Lawes (d,1615) was one of the earliest composers of keyboard suites, By the Restoration the suite was firmly established and developed in the hands of Locke, Blow,Purcell and others. Blow was perhaps the finest harpsichord composer of this period, for in addition to several fine suites he wrote a number of excellent grounds and chacones which are hardly known today. In the early 18th century the French style of Blow and Purcell was replaced by the Italian style; Handel was the leading exponent of this, though other composers, like Loeillet, also helped to introduce it. From this time the suite began to absorb sonata elements, so that by the middle of the 18th century,partly through the influence of Scarlatti and Alberti, suite and sonata were almost indistinguishable. Organ music throughout the period retained a more or less independent repertoire, and the only form, apart from a few psalm preludes, was the voluntary, which developed from the contrapuntal fantasia of the early 17th century. At first generally multi-sectional, this type gradually gave way to works in only one or two sections, such as those of Blow. In the early 18th century the bipartite voluntary gradually split into two distinct movements---an evolutionary process seen clearest in Croft's voluntaries. By about 1740 the two-movement structure had become the norm---a slow movement,usually in the style of Corelli, followed by either a loosely-constructed fugue or a movement emphasising a particular solo stop. Stanley (1713-86) emerged as the leading composer of voluntaries, having fully mastered the form by the age of 213and he continued writing new voluntaries and revising his early ones until his third collection was published in 175).His younger contemporaries composed organ music in a similar style, and it was not until about 1770 that signs of the Classical style began to permeate the voluntary. The music of the period as a whole does not maintain the consistently high standards of the leading Jacobean virginalists, Yet there are many fine individual works: some have long been known in editions of little scholarly value; others have recently been published in several useful editions: while quite a number still await modern edition and performance, as well as detailed studies of how they relate to other works and composers of the period.